Reasonable drug analysis of Listeria monocytogenes meningitis related to mantle cell lymphoma - Guang-Xuan Zhu; Su-Jie Jia (Elsevier, 2019)
We report a case of Listeria meningitis related to mantle cell lymphoma. A clinical pharmacist adjusted repeatedly the patient's anti-infective therapeutic regimen by analyzing the pharmacologic and pharmacokinetic characteristics of antibacterial drugs (such as cefotaxime, meropenem, etc.) due to the patient's repeated fever during hospitalization. To the best of our knowledge, this is the first case of Listeria meningitis related to mantle cell lymphoma treated successfully with meropenem reported in China. This case aims to optimize the anti-infection treatment regimen of Listeria meningitis and to provide a reference for clinicians and clinical pharmacists to use drugs rationally. Keywords: Ampicillin, Listeria monocytogenes, Meningitis, Meropenem